INTERNATIONAL RANKINGS AS AN ASSESMENT TOOL OF THE COMPETETIVENESS OF RUSSIAN UNIVERSITIES - T. Leonova; N. Malanicheva; A. Malanicheva (Вестник университета, 2017)
The article considers the role of the international ranking as an assessment tool of the competitiveness of Russian universities. Currently, joining international rankings results in the improvement of the competitiveness of the university. Under existing circumstances, university management consider university rankings as an important tool of Russian universities’ integration into the world education space. The article describes key areas of the Russian policy in science and education aimed primarily at improvement of positions of Russian universities on the world education market. The article shows current results of the state program «5-100», described its benefits and prospects.